Avaliação e estudo dos comportamentos de orientação social e atenção compartilhada nos transtornos invasivos do desenvolvimento - Montenegro, Margareth Regina Gomes Neves (2007)
Initial Social Communication comprehends skills that appear in early infancy. Among which, Social Orienting (SO) and Joint Attention (JA) have proven to be good predictors of the development of sociability. The impairment of such functions has been strongly associated with the diagnosis of Pervasive Developmental Disorders (PDD). The present study has assessed the initial social communication skills (Social Orienting and Joint Attention) in children from 2 to 4 years old with typical development (n=19) and in children from 3 to 7 years old with Pervasive Developmental Disorder (n=17) paired by mental age. For the assessment the study has developed the PAISC - (Protocol of Assessment of Initial Social Communication). The results from the trials of the protocol have demonstrated that children with Pervasive Developmental Disorder have shown significantly worst performance in the Social Orienting and Joint Attention behaviors if compared to the children with typical development. Among the behaviors, the one that better distinguished children with Pervasive Developmental Disorder from the children with typical development was the Initial Joint Attention. The PAISC protocol allows detecting changes in the development of social communication in the first year of life, being an instrument for the early diagnosis and employment of intervention programs in the cases of Pervasive Developmental Disorders.